The Effect of Educational Game-Based Learning Media on Science Literacy of Grade V Students at SDN 10 Sitiung - Putri, Suci Rahma; Ali, Gunawan; Rahmadhani, Aulia (The Future of Education Journal, 2025)
This study is motivated by the low literacy skills of students during classroom learning activities, particularly in the IPAS subject. One of the problems faced by educators is the limited use of educational game-based learning media, which results in less effective and less engaging learning processes for students. The aim of this research is to enhance students’ thinking abilities, deepen learning motivation, and develop independent learning skills. This study uses a quantitative experimental method, specifically a pre-experimental design with a one-group pretest-posttest model. The instrument used in this research consists of tests given before and after the learning activities. A pretest was administered to assess students' science literacy levels before the use of Wordwall-based educational game media, and a posttest was conducted to determine whether there was an improvement after the intervention. Based on the results, the pretest scores ranged from 15 to 45. After the implementation of Wordwall in the experimental class at SDN 10 Sitiung, Grade V, for the IPAS subject with 13 students, the posttest scores ranged from 65 to 90. These results indicate a significant improvement in students’ science literacy following the use of the educational game-based learning media.